2014
DOI: 10.2174/1381612820666140325105723
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sevoflurane or Remifentanil on the Stress Response to Surgical Stimulus

Abstract: Tissue injury secondary to surgical lesion produces profound changes in endocrine-metabolic function and defence mechanisms in the patient (inflammatory, immunological), leading to an increase in catabolism, immunosuppression and postoperative morbidity. The best anaesthetic and surgical technique should be capable of modulating this response, especially in major surgery, where it can be most harmful and increase patient morbidity. Many of the changes that maintain homeostasis are controlled by the hypothalami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…All of these forms of anesthesia have been found to modulate the immune system and exert effects on innate and adaptive immunity. 712 A comprehensive evaluation of the impact of anesthetic regimens on the immune system can help refine current perioperative management.…”
Section: Introductionmentioning
confidence: 99%
“…All of these forms of anesthesia have been found to modulate the immune system and exert effects on innate and adaptive immunity. 712 A comprehensive evaluation of the impact of anesthetic regimens on the immune system can help refine current perioperative management.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the inhalation of sevoflurane and infusion of remifentanil was a good anesthetic way for laparoscopic operation 10,11 . But many studies also reported that the anesthetic agent could result in POCD 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the type of anesthetic and surgical technique should be modified to control this response, especially in major surgeries in which it can cause the most harm and increase patient morbidity. 20 Opioids are essential drugs that provide the analgesic component of general anesthesia as well as controling the neurovegetative response to surgical trauma. 2 Their ability to reduce the stress response is related to the modulation of nociception in different sites of the neuraxis.…”
Section: Surgical Stress and Immune Suppressionmentioning
confidence: 99%